2020
DOI: 10.1111/jfpe.13345
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable sodium alginate films incorporated with norbixin salts

Abstract: Plastic packaging derived from petroleum may have a negative impact on the environment when it is not properly recycled. Some studies present the use of biodegradable packages developed from natural polymers as a sustainable alternative; thus, the present work aimed to develop biodegradable sodium alginate films with antioxidant properties by the incorporation of carotenoid norbixin. Norbixin salts at the concentration of 0.01-0.05% were added to the sodium alginate films complexed with calcium ions. Carotenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…The optimal SA to PEG ratio is 4 : 1 at which the mechanical strength of SA/PEG/FeCl 3 reaches the maximum. The maximum breaking strength is 26.5 MPa, which is much higher than those reported in the literature (Tables S1) [9–11,16,28,31] . The breaking strain is 3.6 times of that of the pristine SA film and is comparable to those of the modified sodium alginate film reported previously (Table S2).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The optimal SA to PEG ratio is 4 : 1 at which the mechanical strength of SA/PEG/FeCl 3 reaches the maximum. The maximum breaking strength is 26.5 MPa, which is much higher than those reported in the literature (Tables S1) [9–11,16,28,31] . The breaking strain is 3.6 times of that of the pristine SA film and is comparable to those of the modified sodium alginate film reported previously (Table S2).…”
Section: Resultssupporting
confidence: 71%
“…Because of the abundance in nature, easy availability and good degradability, [9][10][11][12][13] sodium alginate is considered as a promising candidate for bioplastic. [14][15][16][17][18][19] In recent years, researches on sodium alginate-based bioplastics have been focused on the addition of various additives (such as cellulose, [20] multi-walled carbon nanotubes [21] ) which may help to improve their mechanical properties or the surface modification (using hydrophobic dodecyltrimethoxysilane, [22] dodecyl glycidyl ether, [23] silica nanoparticles [24] or methyl trimethoxysilane [25] ) which aims to increase its hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinking alginate membranes with CaCl 2 seems to be a strong factor that causes an increase in TS and a decrease in EB [10] , due to Ca 2 + potential to bind polymer chains. Rhim found a TS of 74.9 MPa and an EB of 3.4% for alginate membranes crosslinked by immersion in CaCl 2 2% (w/v) solution, while de Farias et al [26] found TS of 19.84 MPa and EB of 21.26% for alginate 1% (w/v) membranes with glycerol and crosslinked by CaCl 2 1% (w/v) during 5 min. Zactiti and Kieckbusch [27] found TS in a range of 23.11 to 160.26 MPa and EB in a range of 2.16-27.35% depending on the concentration of Ca 2 + solution used and if crosslinking was made in one or two stages.…”
Section: Mechanical Propertiesmentioning
confidence: 97%
“…After drying, 50 ml of a calcium chloride solution (1% w/v) was added to each plate and left for 5 min until the desired cross‐linking was reached. After this period, the liquids were discarded and dried again at 55°C for 45 min (de Farias, Coutinho, Assis, & Rios, 2020). The films without norbixin at a pH of 7.0 and with norbixin at a pH of 3.0, 7.0, and 11.0 were identified as A, B, C, and D, respectively.…”
Section: Methodsmentioning
confidence: 99%